Investigation of the performance of multi-input multi-output detectors based on deep learning in non-Gaussian environments - Mohammad Reza Pourmir; Reza Monsefi; Ghosheh Abed hodtani (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The next generation of wireless cellular communication networks must be energy efficient, extremely reliable, and have low latency, leading to the necessity of using algorithms based on deep neural networks (DNN) which have better bit error rate (BER) or symbol error rate (SER) performance than traditional complex multi-antenna or multi-input multi-output (MIMO) detectors. This paper examines deep neural networks and deep iterative detectors such as OAMP-Net based on information theory criteria such as maximum correntropy criterion (MCC) for the implementation of MIMO detectors in non-Gaussian environments, and the results illustrate that the proposed method has better BER or SER performance.